Ubah gulma menjadi emas: studi kasus pengolahan eceng gondok menjadi humus aktif & enzimatik di Waduk Jatiluhur Purwakarta - Poernama, Teddy; Pebriansyah, Eka; Arifin, Antoni Ludfi; Yusuf, Rully (Universitas Widya Mataram, 2023)
Water hyacinth increase flourishingly and spread rapidly and it potentially harms aquatic ecosystems as it covers water surface and endanger water ecosystems. In Jatiluhur reservoir, the water hyacinth has spread up to 10% of the entire reservoir. Therefore, society's participation in developing active humus/compost and liquid fertilizer from water hyacinth is advantageous for Tirta Emas farmers group in Desa Jatimekar, Kecamatan Jatiluhur, Purwakarta. Furthermore, this study aimed to observe the involvement of PT Pegadaian in the goldifying water hyacinth collaboration program by KUBMN. This study was a literature research as the research was conducted by collecting numerous literature sources such as research articles, books and reports regarding goldifying weeds or water hyacinths and the role of PT. Pegadaian in the program. In the library research, the researchers collected more than 50 research articles, books and study reports regarding water hyacinth's benefits and it's economic potentials. Thus, this study identified that the goldifying program of PT Pegadaian was advantageous in some aspects such as: 1) Ecological aspects: Water environment in Jatiluhur reservoir was better. Because the negative impacts of water hyacinth could be decreased and it was more controllable. 2) Economic aspect: people's income increased as a result of liquid fertilizer from water hyacinth program and sustainable fish cultivation. 3). Social aspect: the beauty of nature in Jatiluhur reservoir without water hyacinth, the emergence of tourist attractions and a harmony relationship between PTJ II as reservoir's manager and people in society.